Photocatalytic degradation of organic pollutants using TiO2-based photocatalysts: A review - Chen, Dongjie; Cheng, Yanling; Zhou, Nan; Chen, Paul; Wang, Yunpu; Li, Kun; Huo, Shuhao; Cheng, Pengfei; Peng, Peng; Zhang, Renchuan; Wang, Lu; Liu, Hui; et al. (Journal of cleaner production, 2020)
Organic compounds, generated from different industries, produce a range of the problematic pollutants in wastewater. TiO2 based photocatalysts are novel materials that exhibit excellent absorption behavior toward organic compounds in wastewater due to their outstanding properties including nontoxicity, high photocatalytic degradation ability, and excellent thermal and chemical stabilities. However, several challenges exist regarding TiO2 applications for organic effluents such as particle aggregation, mass transfer limitation, poor affinity, high band energy, scattering conditions, and difficulty of recovery. Therefore, more design and optimization testing need to be conducted on the treatment conditions in order to reach higher removal efficiencies with lower costs. A variety of parameters of TiO2 based photocatalysts need to be studied: substrate, light intensity, dopant, particle size, structure. These parameters, which affect TiO2 photocatalytic activity on organic pollutants, are discussed in the current review. Thus, making the photocatalyst more anticipated and conducive to further research and development. •Six unique challenges inhibit the application of TiO2 in organic effluents.•Various parameters such as TiO2 forms and substrates were discussed.•High band energy and transfer limitation are the primary limitations.•The key processing parameters are selection of TiO2 substrate and dopant.